SISTEM PERKANDANGAN AYAM BROILER DI JATMIKO FARM - , MEGARIA ARDIANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Enclosure is a building used as a residence animals, a place to do development and cultivation livestock in order to get the benefits and and results. Job Training Poultry Management held in farms Jatmiko located in Sonoharjo, Margokaton, Sayegan, Sleman on December 25 to March 30, 2013. This thesis aims to find a chicken cage system broilers in the tropics and the extent of its application at the farm Jatmiko. The method used for data collection are observation, interview and follow the farm work program Jatmiko. The data have been obtained then compared with the literature. The results obtained include cage system used is a building enclosure conventional, cage type Jatmiko farm is open stage, cage stretching from west to east, there are 4 enclosure maintenance 6 m width, long coop 1 to 4, respectively 45, 33, 27 and 48 m, 2 m high cage and pole height 1.17 m, population 7,500 chicken tail. The walls are made of woven wire cage. The roof of the cage-type simple without a monitor. Floors made of bamboo slats slat type. Equipment enclosure includes chick guard height 40 cm, manual and hanging feeders, place automatic drinking, gasolec and fluorescent lighting with a power 18 watts. Based on the results and discussion, it can be concluded that the system Jatmiko cage farms are good, but there is a lack providing insulation enclosure, keeping the environment clean, damage sections enclosure is not immediately corrected, and the absence of a good biosecurity program.